WORK ENGAGEMENT AS A MEDIATING EFFECT OF PERSONAL RESOURCES ON PERFORMANCE: AN EMPIRICAL STUDY OF WOODCRAFT MSMEs EMPLOYEE - Putimelinda, Widya; Jatmiko, Udik (Strategic Management Business Journal, 2023)
This study explores the phenomenon of MSMEs growth in Tulungagung, with a specific focus on the woodcraft sector. The objective is to understand the relationship between personal resources, work engagement, and employee performance within this MSME context. The sample comprises 126 respondents through purposive sampling. Data were analyzed using descriptive and inferential approach employing Structural Equation Model (SEM) with the SMART-PLS application. The findings indicate that personal resources have a positive impact on both work engagement and employee performance. Additionally, work engagement effectively mediates the influence of personal resources on performance. This study contributes to the understanding of human resource management in MSMEs, highlighting the significance of work engagement as an effective mediator for enhancing employee performance. The implications of this research can serve as a basis for developing human resource management strategies in MSMEs, specifically focusing on improving work engagement and optimizing employee personal resources. JEL Classification: O10, O14, O15